Exploring How Skimming and Scanning Fosters EFL Students’ Reading Comprehension at an English Club Senior High School in Indonesia - Agustin, Lilis; Wisudaningsih, Endah Tri; Fatmawati, Ririn (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
This study aimed to examine the effect of skimming and scanning strategies on improving reading comprehension among students attending the English club at Senior High School Zainul Hasan 1 Genggong. A considerable number of students continue to struggle with reading, an area that is integral to their academic progress and language acquisition. Addressing these challenges necessitates effective teaching tactics to enhance reading comprehension skills, the exploration of which formed the core of this research. The study utilized a pre-experimental research design, focusing on a single group pre-test and post-test methodology. The sample consisted of 30 students who received targeted instruction on skimming and scanning strategies over a determined period. Skimming involves rapidly reviewing a text to get a general idea, while scanning is a technique used for quickly locating specific information within a text. Both strategies are believed to be pivotal in assisting learners to become more efficient and effective readers. Data collected from the pre and post-tests was analyzed using the Paired Sample T-Test. The alternative hypothesis, suggesting that skimming and scanning techniques have no significant effect on reading comprehension, is rejected if the Sig (2-tailed) value is more than 0.05. Conversely, if the Sig (2-tailed) is less than 0.05, the alternative hypothesis is accepted, indicating a significant effect of skimming and scanning techniques on students' reading comprehension. The study's findings revealed that the students who received training in skimming and scanning demonstrated significant improvement in their reading comprehension, substantiating the beneficial impact of these techniques. This improvement is further corroborated by the Sig (2-tailed) value of 0.000, which is less than the critical threshold of 0.05, leading to the acceptance of the alternative hypothesis. The statistically significant results from the Paired Sample T-Test provided robust evidence supporting the efficacy of skimming and scanning techniques in enhancing students' reading comprehension skills. This demonstrates the significance of these strategies in addressing reading comprehension challenges among students and informs the pedagogical approaches for teaching reading in EFL contexts. It underscores the need for their integration in curriculum planning and instruction, thereby contributing substantially to the academic discourse on reading comprehension strategies.